Development of Electronic Student Worksheets Based on Problem Based Learning Using Liveworksheet to Improve the Science Literacy Skills of Elementary School Students - Destini, Frida; Fadhilah Khairani; Siti Nurjanah; Yulistia, Annisa; Syafrudin, Ulwan (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2026)
This study aims to develop and test the feasibility and effectiveness of electronic student worksheets based on Problem Based Learning (PBL) using the Liveworksheet platform in improving the scientific literacy skills of elementary school students. This study uses the Research and Development (R&D) method with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The subjects of the study were 24 fifth-grade students of State Elementary School 10 Metro Timur. Data were collected through expert validation questionnaires, student response questionnaires, and scientific literacy ability tests in the form of pretests and posttests. Data were analyzed using quantitative descriptive techniques, qualitative descriptive techniques, and improvement tests using N-Gain. The results showed that the developed electronic student worksheets obtained a very feasible category from the aspects of material, language, and media. Student responses to the use of electronic student worksheets were in the very good category with a percentage of 91%. The results of the effectiveness test showed an increase in scientific literacy skills with an N-Gain value of 0.72 which is included in the high category. These findings indicate that PBL-based electronic student worksheets using liveworksheet are appropriate, practical, and effective teaching materials to support the improvement of elementary school students' scientific literacy skills.